Role of prophylactic cranial irradiation in patients with limited disease small cell lung cancer: A Danish single institution cohort - Sara Linde; Marianne Maquard Knap; Lone Hoffmann; Azza Ahmed Kahlil; Christina Maria Lutz; Maria Kandi; Lise Saksø Mortensen; Ditte Sloth Møller; Hjørdis Hjalting Schmidt (Acta Oncologica, 2025)
Background and purpose: Prophylactic cranial irradiation (PCI) is part of standard treatment for patients with limited disease small cell lung cancer (LD-SCLC), treated with curative intent. However, doubt has been raised about the efficacy of PCI in a modern clinical setting. Therefore, we examined factors impacting PCI receival, the cumulative incidence of symptomatic brain metastases, and overall survival (OS) with and without PCI.